High-energy-absorption Al-Zn-Mg aluminum alloy profile and preparation method thereof
By controlling the content of Mg and Zn in Al-Zn-Mg aluminum alloy and introducing Er element, high-strength aluminum alloy profiles with excellent energy absorption performance were prepared, solving the problem of insufficient energy absorption performance of 7xxx series aluminum alloys in automotive anti-collision beam components, and improving the safety and fuel efficiency of the material.
Patent Information
- Application Number
- CN202411228276.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-01-10
AI Technical Summary
How to improve the energy absorption performance of 7xxx series aluminum alloys while maintaining their high strength, so as to meet the safety standards of components such as automotive anti-collision beams.
By precisely controlling the content of Mg and Zn in Al-Zn-Mg aluminum alloy, ensuring that 6.9%≤Zn+Mg≤8.0% and the Zn/Mg mass ratio is within the range of 4.9≤Zn/Mg≤7.0, and introducing Er element to form submicron-level dispersed precipitates, combined with two-stage aging treatment, high energy-absorbing aluminum alloy profiles are prepared.
Aluminum alloys with high yield strength and good bending properties can effectively absorb energy during a collision, improving the safety of automotive structural components and fuel efficiency.
Smart Images

Figure BDA0005025317010000081 
Figure BDA0005025317010000082 
Figure BDA0005025317010000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum alloy extruded profiles and relates to a high energy absorption Al-Zn-Mg aluminum alloy profile and a preparation method thereof. Background Art
[0002] As global environmental issues become increasingly severe, energy conservation and emission reduction have become an important issue that the automotive industry cannot avoid. In order to reduce carbon emissions and improve fuel efficiency, automakers are actively seeking various ways to reduce vehicle weight, and the use of lightweight materials is one of the key strategies to achieve this goal. Among many lightweight materials, aluminum alloys are highly favored due to their low density and strong corrosion resistance. In particular, while pursuing higher performance, the safety of automobiles has always been a core issue of concern to consumers, which requires that the material must not only have the characteristics of lightweight, but also must ensure sufficient strength and good energy absorption performance.
[0003] Among aluminum alloy materials, the 6xxx series is widely used in the automotive manufacturing field due to its good formability and high tensile strength. However, with the advancement of technology and changes in market demand, the higher-strength 7xxx series aluminum alloys are gradually emerging. Since the 7xxx series aluminum alloys contain zinc as the main alloying element, they have better mechanical properties, especially higher yield strength. This allows 7xxx aluminum alloys to replace traditional steel or 6xxx aluminum alloys in some key structural parts, such as the anti-collision beam of automobiles.
[0004] In the application of automotive anti-collision beams, aluminum alloy materials with a yield strength in the range of 300 to 400 MPa are usually selected. This level of strength can improve the overall performance by reducing weight while ensuring vehicle safety. However, if the yield strength of the material exceeds 400 MPa, although it can further increase the rigidity of the structure, it will also affect its energy absorption performance during a collision. This is because excessively high yield strength will cause the material to absorb less energy during deformation, which in turn affects the energy absorption effect of the anti-collision beam and cannot meet the safety standards for actual use. Therefore, how to improve the energy absorption performance of the 7xxx series aluminum alloy while maintaining its high strength has become a technical problem that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to address the above problems existing in the prior art and to propose a high energy absorption Al-Zn-Mg aluminum alloy profile with excellent yield strength and three-point bending performance.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A high energy absorption Al-Zn-Mg aluminum alloy profile, wherein the aluminum alloy extruded profile is composed of the following elements in percentage by mass:
[0008] Er: 0.10-0.35%, Mn: 0-0.3%, Cr: 0-0.3%, Cu: 0-0.35%, Fe: 0-0.15%, Si: 0-0.1%, Ti: 0-0.1%, Zr: 0-0.3%, the rest are Al, Zn and Mg and inevitable impurity elements; the contents of Zn and Mg meet the following conditions:
[0009] 6.9wt%≤Zn+Mg≤8.0wt%;
[0010] 4.9≤Zn / Mg≤7.0;
[0011] Zn-4.9Mg≤1.52wt%.
[0012] Yield strength is a measure of the material's ability to begin plastic deformation under stress, while good bending properties indicate that the material can maintain good plasticity and is not easy to break when subjected to external forces. These two properties are crucial for key components such as automotive anti-collision beams. The total content of Mg+Zn in the present invention should be between 6.9% and 8.0%, and the mass ratio of Zn to Mg should be maintained in the range of 4.9≤Zn / Mg≤7.0. In order to further control the content of excess Zn, the present invention also proposes an additional condition: Zn-4.9Mg≤1.36wt%. Through the control of the above conditions, the aluminum alloy material of the present invention can meet the required strength standards while ensuring good energy absorption performance when a collision occurs.
[0013] In the above-mentioned high energy absorption Al-Zn-Mg aluminum alloy profile, the aluminum alloy extruded profile is composed of the following elements in percentage by mass:
[0014] Er: 0.17-0.24%, Mn: 0.07-0.15%, Cr: 0.05-0.12%, Cu: 0.15-0.23%, Fe: 0-0.15%, Si: 0-0.1%, Ti: 0.02-0.1%, Zr: 0.12-0.2%, the rest are Al, Zn and Mg and unavoidable impurity elements;
[0015] The contents of Zn and Mg meet the following conditions:
[0016] 7.0wt%≤Zn+Mg≤7.7wt%;
[0017] 4.9≤Zn / Mg≤6.5;
[0018] 0.35%≤Zn-4.9Mg≤1.36wt%.
[0019] The present invention also provides a method for preparing the above-mentioned high energy absorption Al-Zn-Mg aluminum alloy profile, the method comprising the following steps:
[0020] S1. Prepare raw materials;
[0021] S2, melting the raw materials into cast rods, then homogenizing them, and cooling them to room temperature;
[0022] S3, heating the cast rod, then extruding it, and then water cooling it to room temperature;
[0023] S4. Finally, double-stage aging treatment is carried out.
[0024] In the above method for preparing a high energy absorption Al-Zn-Mg aluminum alloy profile, the melting temperature in step S2 is 730-790°C.
[0025] Preferably, the melt is deslagging and analyzed before furnace during smelting, and then the melt is refined, degassed and filtered online. The temperature in the incubator is controlled at 710-730°C, the flow channel temperature is controlled at 680-710°C, and the liquid aluminum alloy melt is cast into round cast bars.
[0026] In the above-mentioned method for preparing a high energy absorption Al-Zn-Mg aluminum alloy profile, the homogenization treatment temperature in step S2 is 460-530° C. and the time is 6-10 hours.
[0027] In the above method for preparing a high energy absorption Al-Zn-Mg aluminum alloy profile, the heating temperature in step S3 is 480-520°C.
[0028] In the above-mentioned method for preparing a high energy absorption Al-Zn-Mg aluminum alloy profile, the aging treatment is a double-stage aging treatment.
[0029] Preferably, in the double-stage aging treatment, the first-stage aging temperature is 100-120°C, and the time is 6-10h; the second-stage aging temperature is 145-165°C, and the time is 8-15h.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The present invention achieves unique properties of both high strength and good plasticity by precisely controlling the ratio of alloy elements. The content of Mg and Zn in the aluminum alloy needs to meet specific conditions: the total content of Mg+Zn should be between 6.9% and 8.0%, and the mass ratio of Zn to Mg should be maintained in the range of 4.9≤Zn / Mg≤7.0. In order to further control the content of excess Zn, the present invention also proposes an additional condition: Zn-4.9Mg≤1.36wt%. In this way, an aluminum alloy material with excellent yield strength and good bending properties can be obtained.
[0032] 2. In addition to controlling the content of Mg and Zn, the present invention also introduces the Er (erbium) element. The Er element can form submicron-level dispersed precipitates with Al. These precipitates can effectively inhibit the recrystallization of the material during processing, thereby making the microstructure of the alloy finer. The refined microstructure can not only reduce the thickness of the coarse-grained layer on the surface of the extruded profile, but also significantly improve the plasticity of the material. According to the requirements of the present invention, the Er content should be controlled between 0.17% and 0.24% to ensure that the yield strength and three-point bending performance of the alloy reach the optimal state.
[0033] 3. The present invention has successfully developed an Al-Zn-Mg aluminum alloy material with high yield strength and excellent bending performance by precisely controlling the contents of the three elements Mg, Zn and Er. This material can not only meet the strength and energy absorption requirements of key components such as automotive anti-collision beams, but also reduce the weight of the vehicle to a certain extent, which helps to improve the overall performance and fuel efficiency of the vehicle. By adopting this new aluminum alloy material, automobile manufacturers can better cope with environmental and safety challenges and promote the automotive industry to develop in a greener and more sustainable direction.
[0034] 4. The high energy absorption Al-Zn-Mg aluminum alloy profile Rm≥420MPa prepared by the present invention can ensure that the structural parts can maintain integrity and safety when bearing loads under various working conditions; the high yield strength Rp0.2≥400Mpa can help the structural parts better absorb impact energy; A50≥12% can ensure that in the event of accidents such as collisions, the structural parts can absorb more energy through plastic deformation and improve overall safety; the three-point bending pressure ≥320mm ensures that the structural parts can maintain good shape stability when bearing bending loads and are not prone to brittle fracture. DETAILED DESCRIPTION
[0035] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.
[0036] In some embodiments of the present invention, the aluminum alloy comprises the following components in mass percentage:
[0037] Mn≤0.30wt%;
[0038] Cr≤0.30wt%;
[0039] Cu≤0.35wt%;
[0040] Fe≤0.15wt%;
[0041] Si≤0.10wt%;
[0042] Ti≤0.10wt%;
[0043] Zr≤0.30wt%;
[0044] Er: 0.10-0.35wt%;
[0045] The rest are unavoidable impurity elements and Al; the individual content of the impurity elements is ≤0.05wt%, and the total content is ≤0.15wt%.
[0046] Among them, 6.9≤Zn+Mg≤8.0;
[0047] 4.9≤Zn / Mg≤7.0;
[0048] Zn-4.9Mg≤1.52wt%.
[0049] Mg and Zn are the main additive elements in 7xxx alloys. During the aging process, Mg and Zn precipitate to form strengthening phases such as GP zone, η' and η phase, among which η' is the main strengthening precipitation phase in the alloy. The Zn / Mg atomic ratio is 0.9-1.8, wherein the relative atomic mass of Mg is 24, and the relative atomic mass of Zn is 65, which is converted into a mass ratio of (2.4-4.9):1. In the composition design, if the Zn / Mg ratio is seriously lower than this ratio range, it will cause Mg excess, which will not have a significant strengthening effect, but may segregate at the grain boundary and cause grain boundary embrittlement, which will cause brittle fracture of the material and reduce the bending performance of the material. Therefore, the present invention takes the lower limit of the Zn / Mg mass ratio as 4.9:1 to control the excess Mg. Comparing the results of Comparative Example 1 and Example 1 in Table 1 and Table 2, it is verified that Mg excess is not good for the three-point bending performance of the alloy. However, it was found in production that when the Zn / Mg mass ratio is too high, the quenching sensitivity will increase. At the same time, the inhibitory effect of pre-aging on the precipitation of the second phase with a high Zn / Mg mass ratio is weak, which is not conducive to subsequent heat treatment and processing. Therefore, the present invention takes the upper limit of the Zn / Mg mass ratio as 7.0:1, that is, the present invention takes the Zn / Mg mass ratio range as 4.9-7.0.
[0050] Since the upper limit of the mass ratio of Zn / Mg of the strengthening phase η' is 4.9:1, and as the excess Zn increases, the GP zone precipitates slower from the matrix, and more GP zone and η' phase can be retained, but the excess Zn element is too much, this gain effect will be weakened, and the quenching sensitivity of the alloy will be increased and the extrudability will be reduced. Comparing the results of Example 1-3 and Comparative Example 1-2, it is found that when the excess Zn content exceeds 1.36%, the increase in excess Zn will no longer improve the performance of the alloy, and the toughness of the alloy will decrease. Therefore, in order to control the content of excess Zn, the present invention takes Zn-4.9Mg≤1.36.
[0051] From the mechanical properties of the aluminum alloy prepared in Example 1 and Comparative Example 3 in Table 1 and Table 2, it can be seen that when the total amount of Mg+Si is less than 6.9%, the mechanical properties cannot meet the requirement of 400MPa due to insufficient strengthening phase in the alloy. Comparing the mechanical properties of Example 4 and Comparative Example 4 in Table 1 and Table 2, it can be seen that when the total amount of Mg+Si exceeds 8%, the strength of the alloy is significantly improved, but the toughness of the alloy decreases, and the downward pressure of three-point bending cannot meet 320mm, so the Mg+Zn content of the present invention is controlled within the range of 6.9-8.0%.
[0052] In summary, the design of Mg and Zn in the present invention follows the following rules:
[0053] Total content of Mg+Zn: 6.9-8.0wt%; mass ratio of Zn / Mg: 4.9-7.0; excess Zn content: Zn-4.9Mg≤1.52.
[0054] The present invention further controls the contents of Mg and Zn as follows:
[0055] Total content of Mg+Zn: 7.0-7.7wt%; mass ratio of Zn / Mg: 4.9-6.5; excess Zn content: 0.35wt%≤Zn-4.9Mg≤1.36wt%. Further controlling the content of Mg and Zn within the above range will obtain better performance.
[0056] Fe and Si are impurity elements in 7 series aluminum alloys. During the melting and casting process, brittle and coarse Al-Fe-Si phases will be generated. The tip of the Al-Fe-Si phase causes stress concentration, becomes the initiation source of cracks, and reduces the fracture toughness of the material. Therefore, the Fe content is controlled below 0.15%, and the Si content is controlled below 0.1%.
[0057] Mn and Cr elements will generate dispersed phases during the production process, hindering the migration of dislocations, inhibiting the nucleation and growth of recrystallization, and playing a role in refining grains. At the same time, Mn elements will transform the brittle and coarse AlFeSi phase in the matrix into the AlFeMnSi phase, reducing the negative impact of the AlFeSi phase and improving the mechanical properties of the alloy. However, if the content of Mn and Cr is too high, the quenching sensitivity of the alloy will be increased. In addition, the η phase will precipitate in the Cr-rich phase, resulting in a reduction in the effective strengthening phase η' phase, causing the alloy strength to decrease; excessive Mn causes the AlFeMnSi phase to coarsen, reducing the forming performance of the alloy. Therefore, the content of Mn elements is further controlled at 0.07-0.15%, and the content of Cr elements is further controlled at 0.05-0.12%.
[0058] The Al3Zr dispersed phase formed by the Zr element and the Al matrix is small in size and has a more effective grain refinement effect than Mn and Cr. In addition, the Al3Zr phase is coherent with the matrix, which greatly increases the difficulty of precipitation of the equilibrium phase near the Al3Zr phase and solves the problem of quenching sensitivity. However, too high a Zr content will cause segregation of Zr elements, resulting in uneven distribution of Al3Zr, which will reduce the performance of the alloy. Therefore, the Zr content is further controlled at 0.12% to 0.20%.
[0059] The Er element can form an Al3Er dispersed phase that is coherent or semi-coherent with the matrix, which plays a role in refining grains and inhibiting recrystallization. In alloys containing Zr, Er and Zr can work together to form Al3(Er, Zr), which plays a more significant role. During the melting and casting process, the primary Al3(Er, Zr) plays a role in refining the cast grains. At the same time, Er has a high chemical activity and combines with the H element in the aluminum liquid to form hydrides, reducing the content of free hydrogen in the aluminum liquid and the porosity in the cast rod, thereby improving the strength and toughness of the alloy; during the aging process, the secondary Al3(Er, Zr) phase is coherent with the matrix, promoting the precipitation of η' and better pinning dislocations, thereby improving the strength of the alloy. However, if the Er content is too high, segregation will occur, resulting in deterioration of the alloy's performance. As shown in Examples 5-8 in Tables 1 and 2, as the Er content increases from 0.08% to 0.24%, the strength and maximum pressing amount of the alloy increase, and the bending performance improves; when the Er content increases from 0.24% to 0.27%, the strength and performance of the alloy do not improve, but instead decrease due to the segregation of the Er element, so the Er element content is further controlled at 0.17% to 0.24%.
[0060] Cu plays an important role in ultra-high strength aluminum alloys. On the one hand, it forms Al2Cu phase to improve the strength of the alloy; on the other hand, it can reduce the potential difference between the grain boundary and the grain, form a non-precipitation zone at the grain boundary, interrupt the continuity of the grain boundary, and improve the corrosion performance along the grain. However, too high Cu content will greatly reduce the extrudability and plasticity of the alloy. Therefore, the Cu content is further controlled at 0.15% to 0.23%.
[0061] The Ti element mainly refines the grains during the casting process and can also improve the alloy's resistance to welding cracks. Therefore, the Ti element content is further controlled to be 0.02% to 0.10%.
[0062] The technical scheme of the present invention is further described below by specific examples, but it does not constitute a limitation of the present invention. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in this field, and the methods used in the embodiments are all conventional methods in this field.
[0063] Embodiment 1-8:
[0064] S1. The aluminum alloy profile compositions of Examples 1-12 are configured as shown in Table 1;
[0065] S2, adding the prepared remelting aluminum rod and master alloy into the melting furnace for melting at 750°C, removing slag from the melt, and performing furnace analysis; performing online refining, degassing and filtering on the melt, controlling the temperature in the heat preservation box to 710°C, the flow channel temperature to 690°C, and casting the liquid aluminum alloy melt into round casting rods;
[0066] S3, cutting off the head and tail of the round ingot, keeping the temperature at 490°C for 6 hours, and then cooling to room temperature;
[0067] S4, heating the treated round ingot to 500° C., then extruding and water cooling to room temperature;
[0068] S5. The cooled aluminum profile is subjected to double-stage aging treatment in an aging furnace.
[0069] The aging treatment steps are: 115℃×8h+155℃×10h.
[0070] Comparative Examples 1-4:
[0071] The only difference from Example 1 is that the alloy elements of Comparative Examples 1-4 are as shown in Table 1.
[0072] Table 1: Aluminum alloy composition ratios of Examples 1-8 and Comparative Examples 1-4
[0073]
[0074] Table 2: Mechanical and bending properties test results of aluminum alloys prepared in Examples 1-8 and Comparative Examples 1-4
[0075]
[0076]
[0077] In summary, the present invention achieves unique properties of both high strength requirements and good plasticity by precisely controlling the ratio of alloy elements. The content of Mg and Zn in the aluminum alloy needs to meet specific conditions: the total content of Mg+Zn should be between 6.9% and 8.0%, and the mass ratio of Zn to Mg should be maintained in the range of 4.9≤Zn / Mg≤7.0. In order to further control the content of excess Zn, the present invention also proposes an additional condition: Zn-4.9Mg≤1.36wt%. In this way, an aluminum alloy material with excellent yield strength and good bending properties can be obtained.
[0078] The parts of the embodiments herein that are not exhaustive of the midpoint values of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the listed or unlisted embodiments of the scheme of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.
[0079] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical schemes composed of any combination of the above technical features. The above is a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.
[0080] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A high energy absorption Al-Zn-Mg aluminum alloy profile, characterized in that: The aluminum alloy profile is composed of the following elements in percentage by mass: composition: Er: 0.10-0.35%, Mn: 0-0.3%, Cr: 0-0.3%, Cu: 0-0.35%, Fe: 0-0.15%, Si: 0-0.1%, Ti: 0-0.1%, Zr: 0-0.3%, the rest are Al, Zn and Mg and inevitable impurity elements; the contents of Zn and Mg meet the following conditions: 6.9wt%≤Zn+Mg≤8.0wt%; 4.9≤Zn / Mg≤7.0; Zn-4.9Mg≤1.52wt%.
2. The high energy absorption Al-Zn-Mg aluminum alloy profile according to claim 1, characterized in that: The aluminum alloy profile is composed of the following elements in percentage by mass: composition: Er: 0.17-0.24%, Mn: 0.07-0.15%, Cr: 0.05-0.12%, Cu: 0.15-0.23%, Fe: 0-0.15%, Si: 0-0.1%, Ti: 0.02-0.1%, Zr: 0.12-0.2%, the rest are Al, Zn and Mg and unavoidable impurity elements; The contents of Zn and Mg meet the following conditions: 7.0wt%≤Zn+Mg≤7.7wt%; 4.9≤Zn / Mg≤6.5; 0.35%≤Zn-4.9Mg≤1.36wt%.
3. A method for preparing a high energy absorption Al-Zn-Mg aluminum alloy profile according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: S1. Prepare raw materials; S2, melting the raw materials into cast rods, then homogenizing them, and cooling them to room temperature; S3, heating the cast rod, then extruding it, and then water cooling it to room temperature; S4. Finally, double-stage aging treatment is carried out.
4. The method for preparing a high energy absorption Al-Zn-Mg aluminum alloy profile according to claim 3, characterized in that: The melting temperature in step S2 is 730-790°C.
5. The method for preparing a high energy absorption Al-Zn-Mg aluminum alloy profile according to claim 3, characterized in that: The homogenization temperature in step S2 is 460-530°C and the time is 6-10h.
6. The method for preparing a high energy absorption Al-Zn-Mg aluminum alloy profile according to claim 3, characterized in that: The heating temperature in step S3 is 480-520°C.
7. The method for preparing a high energy absorption Al-Zn-Mg aluminum alloy profile according to claim 3, characterized in that: The aging treatment is a double-stage aging treatment.
8. The method for preparing a high energy absorption Al-Zn-Mg aluminum alloy profile according to claim 7, characterized in that: In the double-stage aging treatment, the first-stage aging temperature is 100-120°C and the time is 6-10h; the second-stage aging temperature is 145-165°C and the time is 8-15h.